Impact of randomness on MAC layer schedulers over high speed wireless campus network in IEEE802.11e - Alam, M. K.; Latif, Suhaimi A; Akter, M.; Arafat, M. Y. (IJCSSE, 2014)
IEEE802.11e standard provides an EDCA mechanism to ensure the QoS using service differentiation function for IMM trafficsthrough the WCN. In an EDCA mechanism, IMM traffics have been classified into four categories and each category has specific priority. Many EDCA schedulers allow these traffics to access the channel based on assigned priorities. The IMM high priority traffic is high delay sensitive and required high bandwidth to ensure QoS over the networks. Scheduling mechanism is the effective way to satisfy IMM traffic but it cannot give guarantee because of the randomness of some EDCA schedulers or proposed networks. In order to provide the QoS,scheduling mechanism is the challenging issue to transmit IMM traffic through the channel and it is still need to be solved over WCN. This work aims to examine the effect of the randomness on different MAC layer schedulers' performance and evaluates the performance of the proposed schedulers using different performance metrics in WCN.